Corporation tax 1980-81 - Harris, David R.; Sutcliffe, John W. (Croydon, England : Tolley Publishing Co. Ltd., 1980)
This editions contained all the provisions relevant to corporation tax, including those of the Finance Act 1980, extra-statutory concession, revenue statements, case law and other information to 31 July 1980.
Includes index.
ne 09/04/2019
Loans
Keywords: Corporate income tax; Corporate income tax--Law.; Taxation